The effect of nectar production to the gathering behaviour of honeybees and to the foraging activity of wild bees at apple flowers - Benedek, P.; Finta, K. (International Journal of Horticultural Science, 2006)
Intensity of bee visitation (honeybees and wild bees), foraging behaviour of honeybees and nectar parameters (nectar production, sugar concentration, sugar content in nectars) were inspected at 18 apple cultivars for three consecutive years. Honeybee visitation was calculated to be some 3.07 bee visits at a single apple flower a day but wild bee activity was very low, only some 0.11 wild bee visits per flower per day. The nectar production (nectar content) of apple flowers was fairly different according to the cultivars and the nectar production (nectar content) of flowers was negatively correlated with the sugar concentration in nectar. Interestingly, at the majority of the inspected 18 cultivars the nectar production has shown minor or no changes in the morning and at the afternoon. The nectar production (nectar content) of flowers clearly encouraged the total bee activity at the inspected cultivars (r = 0.54). Bees visited abundant nectars with greater sugar concentration most intensely than lees abundant nectars with smaller sugar concentration. Nectar parameters, however, affected the activity of honeybees with different types of gathering behaviour in different way. More intense activity by pollen gatherer and mixed behaviour honeybees was observed at cultivars producing abundant nectar (pollen gatherers: r = 0.65, mixed behaviour: r = 0.79). The activity of pollen gatherer honeybees and of mixed behaviour bees, on the other hand, was negatively correlated to the sugar concentration in nectar (pollen gatherers: r = -0.51, mixed behaviour: r = -0.73). This can be explained by the fact that their behaviour was much more affected by the amount of pollen than by any nectar parameters. Accordingly, "mixed behaviour honeybees" should probably rather be called as "pollen gatherers with nectar load" instead of "nectar gatherers with pollen load", as widely used in literature. The activity of ineffective side worker nectar gatherers was greatly encouraged by the sugar concentration in nectar (p = 0.63), similarly to the pure (top) nectar gatherer honeybees (r = 0.72). There was a negative relationship between the nectar production (nectar content) of flowers and the activity of these behaviour classes (nectar gatherers: r = -0.47, side workers: r = -0.36). Concluding the findings we can state that the activity of pollen gatherers and mixed behaviour honeybees is strongly encouraged by greater nectar production (greater nectar content) of apple flowers. Their activity, however, is mostly dependent firstly on the amount of pollen. This is the reason why the sugar concentration is in a negative relationship to the activity of pure pollen gatherers and mixed behaviour bee. On the other hand, pure nectar gatherers and side worker nectar gatherers are greatly encouraged by the sugar concentration of apple nectar the amount of nectar was not a definite influence on their activity. Side worker honeybees occurred at each cultivar inspected, however, their ratio varied widely among cultivars. So we can draw the conclusion that, in contradiction with earlier believes, side worker nectar gathering is a general phenomenon at apple flowers. The activity of side workers depends first of all on the relative position of stamens and petals; however, low sugar concentration of nectars can probably moderate their activity but probably do not affect pollen gatherers and mixed behaviour bees. Wild bee visitation was very low; the wild bee species observed (Osmia cornuta, Andrena flavipes, Anthophora acervorum, Bombus terrestris, Bombus lapidarius and Halictus simplex) comprised some 3.44 per cent of the total bee visitation at apple flowers only. Wild bee visitation was in a positive correlation with the nectar production (nectar amount) of flowers (r = 0,4) and with the sugar content of nectar (r = 0.46) but it was negatively correlated with the sugar concentration in nectar (r = -0,27). Our result calls the attention to the importance of nectar parameters in the effective honeybee pollination of apple plantations. Most effective pollinating activity of honeybees can be expected in plantations with cultivars of high nectar production because this feature seem so encourage the activity of those behaviour classes (pure pollen gatherers and mixed behaviour bees) that are the most effective pollinating agents among honeybees.